Tectonic changes in the wage formation system in Greece - Ιωάννου, Χρήστος Α. (The Greek Review of Social Research, 2011)
The Greek wage formation system suffers the consequences of both exogenous and endogenous factors. These are related on the one hand, with the repercussions of the global financial crisis that led to the new historic employment crisis, and on the other hand, with the domestic aspects of public sector debt insolvency. In fact, the Greek wage formation system suffers as a result of of the challenges that remained undealt with during the last twenty years with regard to the collective bargaining structures and processes and to the wage formation system. Unmet challenges that, in the context of the current crisis, may imply tectonic changes in the wage formation system. The passage from a system of collective regulation of wage formation to a system of individual regulation of wage formation constitutes the more likely consequence of these tectonic changes. This is not a tendency that should be attributed to a dominant exogenous trend in the wider European framework for employment relations regulation; rather, it is mainly associated with the collapse of the domestic legal-administrative system of wage formation which has been based on law 1876/90.